Questões teóricas e metodológicas das pesquisas com crianças: algumas reflexões - Cordeiro, Ana Paula [UNESP]; Penitente, Luciana Aparecida de Araújo [UNESP] (My University, 2014)
Thinking about research with children, giving time and voice to them is a discussion that is still fresh. Thus, in order to establish some reflections on the theoretical and methodological issues in research with children, we hope with this article to give visibility to the theoretical assumptions of authors who are concerned to place the child and childhood in the center of the research process. Thus, contributing to this discussion, this text is divided into three stages: initially bring some contributions of sociology of childhood and the various fields of knowledge to think about research with children. Secondly, we propose to discuss some methods and procedures that may favor the development of research with children. When we trace the historical development related to research with children and recover the concept of childhood and child while being active and producer of culture, we headed for the third time this work presents some results and conclusions, which can direct our gaze on pursuit of research instruments that capture what children think, feel and build in the world that they live and live together.

Pensar a pesquisa com crianças, dando vez e voz a elas é uma discussão que se faz ainda recente. Com o intuito de estabelecer algumas reflexões em torno das questões teóricas e metodológicas das pesquisas com crianças esperamos, com esse artigo dar visibilidade a pressupostos teóricos de autores que se preocupam em colocar a criança e a infância no centro do processo de pesquisa. Contribuindo com essa discussão, esse texto será dividido em três momentos: inicialmente trazemos algumas contribuições da Sociologia da Infância e das diversas áreas do conhecimento para pensar a pesquisa com crianças. Num segundo momento, nos propomos a discutir alguns métodos e procedimentos que podem favorecer o desenvolvimento das pesquisas com crianças. Ao traçar a evolução histórica relacionada às pesquisas com crianças e resgatar a concepção de infância e de criança enquanto ser ativo e produtor de cultura, nos dirigimos para o terceiro momento do trabalho, apresentando alguns resultados e conclusões desse estudo, que podem orientar o nosso olhar na busca de instrumentos de pesquisas capazes de captar o que as crianças pensam, sentem e constroem no mundo em que vivem e convivem.
Theoretical and methodological issues in research with children: some reflections
Keywords: educação; infância; criança